The other Kuala Lumpur : living in the shadows of a globalising Southeast Asian city - Yeoh, Seng Guan; Lepawsky, Josh, 1972- (b New York : Routledge, 2014)
'Kuala Lumpur, like many Southeast Asian cities, has changed very significantly in recent decades--expanding its size,'modernising' and'globalising'. For many people these changes represent'progress'. This book, however, focuses on the more marginalised sections of society, especially those people whose lives have been adversely affected by recent changes. It considers how the everyday lives of the marginalised in society have been affected by recent changes, showing how urban renewal, the law, and Malay nationalism and Islamicisation often work against many of these marginal groups, and examining how they struggle to survive'--
Introduction : the world class city and subaltern Kuala Lumpur / Yeoh Seng Guan -- Globalising Kuala Lumpur and rationalising the street : hawkers and the aporias of urban renewal along Petaling Street and Jalan Masjid India / Josh Lepawsky and Rodney Jubilado -- Can law do justice? : everyday ethics and the transformation of urban life in Kuala Lumpur / Richard Baxstrom -- Citizenship and the city : visions and revisions of Malaysia / Julian C.H. Lee -- The moderate and the excessive : performing Malay consumption / Johan Fischer -- Housing Hindu deities in urban landscapes : insights from Singapore and Kuala Lumpur / Vineeta Sinha -- Seeking refuge in Kuala Lumpur : personal and collective strategies to relieve vulnerability amongst asylum seekers, refugees and stateless persons / Alice M. Nah -- The creation of sexual dissidence in Kuala Lumpur : the case of Seksualiti Merdeka / Julian C.H. Lee -- The last plantations in Kuala Lumpur / S. Nagarajan and Andrew Willford.
Includes bibliographical references and index.
Keywords: Marginality, Social -- Malaysia -- Kuala Lumpur; Sociology, Urban -- Malaysia -- Kuala Lumpur; Kuala Lumpur (Malaysia) -- Social conditions